2022
DOI: 10.3389/fgene.2022.987238
|View full text |Cite
|
Sign up to set email alerts
|

A p53 transcriptional signature in primary and metastatic cancers derived using machine learning

Abstract: The tumor suppressor gene, TP53, has the highest rate of mutation among all genes in human cancer. This transcription factor plays an essential role in the regulation of many cellular processes. Mutations in TP53 result in loss of wild-type p53 function in a dominant negative manner. Although TP53 is a well-studied gene, the transcriptome modifications caused by the mutations in this gene have not yet been explored in a pan-cancer study using both primary and metastatic samples. In this work, we used a random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In addition to this, integration with SHAP values provides new insights into the effects of each feature on outcomes. Our rank-based permutation approach was also applied in a study by Keshavarz-Ragahi et al (includes Kolisnik) [27] to identify multiple key features associated with p53 activity, enhancing the understanding of TP53-related transcriptional signatures across various cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, integration with SHAP values provides new insights into the effects of each feature on outcomes. Our rank-based permutation approach was also applied in a study by Keshavarz-Ragahi et al (includes Kolisnik) [27] to identify multiple key features associated with p53 activity, enhancing the understanding of TP53-related transcriptional signatures across various cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…The development of machine learning technology may come with an easier answer to the future of cancer treatment. Recently a study using such technology reported new genes ( GPSM2, OR4N2, CTSL2, SPERT, RPE65 ) that may be associated with p53 functions, which seem to be a better fit for the platinum-based therapies for patients than their TP53 status [ 104 ]. The ongoing discussion between researchers on whether personal therapy, which considers the investigation of molecules targeting the exact type of mutation of TP53 , should be pursued or not has yet to be unraveled [ 105 , 106 , 107 , 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, with its acquired oncogenic capabilities, mutated p53 can be regarded as a renegade p53, and therefore it is essential to comprehend individual mutations in the gene before seeking associations between TP53 mutations and patient outcomes. After a long debate, it was postulated that each TP53 mutation has context-specific effects in response to different cancer therapeutics used [14,15].…”
Section: Tp53-tumor Suppressor Gene That Encodes P53 Protein In Ovari...mentioning
confidence: 99%